METODE ANALISIS KUALITATIF DAN KUANTITATIF LDL-C MENGGUNAKAN ELEKTROFORESISAGAROSE DAPAR TAE (TRIS-ASAM ASETAT-EDTA) - Setyari, Putu Rosi; Wirasutha, IMA Gelgel; Junitha, I Ketut (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012, 2013)
In this research had been done the development of analysis qualitative and quantitative methods of LDL-C in human serum using agarose electrophoresis. The methods that had been developments are separation lipoprotein in human serum using agarose electrophoresis with TAE pH 8,6 buffer system and quantification methods for LDL-C using spectrophotometer UV-Vis. The aim of this research is to find out a simple method that can separate lipoproteins of human serum and quantificating LDL-C. The results of this research shows agarose electrophoresis with TAE pH 8,6 buffer system could  separate LDL-C in human serum as good as electrophoresis with Na-Barbital buffer system. However, for its quantification only can be done with spectrophotometer UV-Vis.
Keywords: LDL-C, lipoproteins, electrophoresis, separation